1985
DOI: 10.2307/1956118
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Representativess and Voting: An Assessment of the Impact of “Choices” vs. “Echoes”

Abstract: The persistent decline in voting in presidential elections since 1960 has resulted in serious scholarly attention being given to nonvoting. Despite the quality of these studies, however, the ratio of what we know about nonvoting to what we do not know is rather low. In the hopes of improving this situation, I advance the hypothesis that one reason that individuals do not vote is that their interests are not represented by any of the major candidates. To test this hypothesis, I used the SRC election studies (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 21 publications
1
45
1
1
Order By: Relevance
“…And in particular, would they be less likely to vote in races where they were denied a chance to vote for a copartisan? Zipp (1985) found that voters who were not given at least one desirable candidate to vote for were less likely to turn out, and examining elections from 1972 thru 2008 Leighley and Nagler (2014) find some evidence to support Zipp's claim. Table 8 gives the abstention rate for orphaned voters in the State Assembly Race versus the abstention rate for non-orphans.…”
Section: Impact On General Election Behaviormentioning
confidence: 99%
“…And in particular, would they be less likely to vote in races where they were denied a chance to vote for a copartisan? Zipp (1985) found that voters who were not given at least one desirable candidate to vote for were less likely to turn out, and examining elections from 1972 thru 2008 Leighley and Nagler (2014) find some evidence to support Zipp's claim. Table 8 gives the abstention rate for orphaned voters in the State Assembly Race versus the abstention rate for non-orphans.…”
Section: Impact On General Election Behaviormentioning
confidence: 99%
“…4 Adams and Merrill (2003) offer empirical support for their argument using data on U.S. presidential elections. Further, there is considerable empirical evidence that supports the link between participation and candidate positions (Zipp 1985;Plane and Gershtenson 2004).…”
Section: Ideological Heterogeneity and Divergencementioning
confidence: 99%
“…For example, when potential voters in an American presidential campaign were indifferent to the candidates they did not vote (Brody and Page, 1973). Those who perceived the candidates' views as equally distant from their own, regardless of the direction of that difference, were less likely to vote (Zipp, 1985). Further, as people perceived fewer differences between political parties abilities to solve problems, they were less likely to vote (Southwell, 1985).…”
Section: Introductionmentioning
confidence: 99%